Bluetooth Low Energy-based Adaptive Scheme for IoT Services - Shan, Gaoyang; Choi, Geunkyung; Roh, Byeong Hee (International Conference on Ubiquitous and Future Networks, ICUFN, 2023)
To adapt to various IoT services, Bluetooth Low Energy (BLE) specification has defined a variety of communication modes, such as advertising, extended advertising, and periodic advertising events. As services' environments, such as the number of users and QoS requirements, are changed, modes of protocols should be also adjusted to meet those services' needs. This paper proposes an adaptive BLE scheme to reflect dynamically changing services' environments. The effectiveness of the proposed scheme is verified through simulation experiments.
Keywords: Adaptive scheme; Advertizing; Advertizing event; Bluetooth low energy; Energy-based; IoT; Lower energies; Service environment; Adaptive Scheme; Advertising Events; BLE; Bluetooth Low Energy; Internet of Things; IoT